2024
DOI: 10.1136/jnis-2023-021126
|View full text |Cite
|
Sign up to set email alerts
|

Technique and impact on first pass effect primary results of the ASSIST global registry

Rishi Gupta,
Salvador Miralbés,
Angel Calleja Bonilla
et al.

Abstract: BackgroundPatients treated with mechanical thrombectomy (MT) for acute ischemic strokes from large vessel occlusion (LVO) have better outcomes with effective reperfusion. However, it is unknown which technique leads to better technical and clinical success. We aimed to determine which technique yields the most effective first pass reperfusion during MT.MethodsIn a prospective, multicenter global registry we enrolled patients treated with operator preferred MT technique at 71 hospitals from January 2019 to Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
0
4
2
Order By: Relevance
“…No difference in total procedure time was found although aspiration based thrombectomy was faster in the FPR group. 6 In contrast with our results, previous studies have not found any association between the firstline method and clinical outcome in anterior circulation stroke. 5 10 However, most previous studies have been of limited size and/or designed as clinical trials, not necessarily reflecting the true clinical patient panorama.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No difference in total procedure time was found although aspiration based thrombectomy was faster in the FPR group. 6 In contrast with our results, previous studies have not found any association between the firstline method and clinical outcome in anterior circulation stroke. 5 10 However, most previous studies have been of limited size and/or designed as clinical trials, not necessarily reflecting the true clinical patient panorama.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent randomized studies have suggested that stent retriever and aspiration based thrombectomy perform similarly regarding the FPR rate while other observational studies have shown differences. [3][4][5][6] Further, there is no consensus on whether the methods differ in technical and clinical outcomes when FPR or MPR is achieved. 5 Experience of the operator might predict FPR, and the learning curve of the methods might differ, indicating that high volume center analysis is needed to compare true effects.…”
Section: Ischemic Strokementioning
confidence: 99%
“…This Registry aimed to assess the procedural success and clinical outcomes associated with various techniques for mechanical thrombectomy in LVO in the anterior circulation. 19 It included data from 1492 patients enrolled in 71 North American, European, and Asian centers from January 2019 to May 2022. See primary publication for further details.…”
Section: Methodsmentioning
confidence: 99%
“…See primary publication for further details. 19 Inclusion and exclusion criteria can be found in the supplement.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, currently available thrombectomy devices to date can only achieve FPR rates ranging from 30 to 60% 10,11,12 . The simultaneous double stent-retriever (double-SR) technique was first proposed as a rescue therapy after multiple failed attempts to retrieve a refractory thrombus with a single-SR 13,14 .…”
Section: Introductionmentioning
confidence: 99%